Kecanduan Game Online dan Identitas Diri, Interaksi Sosial serta Perilaku Agresif Remaja - Rahmat Muhazir; Teuku Tahlil; Hilman Syarif (Jurnal Keperawatan Silampari, 2023)
This study aims to identify the relationship between online game addiction and adolescents' self-identity, social interaction, and aggressive behavior. This research method is a quantitative study with a cross-sectional survey design. This study's results indicate that most adolescents are male (50.1%) and are in class IX (38.3%). The average age of the respondents was 13.34 years with an SD of 0.900, an allowance of IDR 10,088.47 thousand with an SD of 4020.806, and the length of time playing games in a day was 1.546 with an SD of 1.973. The results of bivariate analysis obtained p-values for adolescent self-identity (p=0.391), social interaction (p=0.000), and adolescent aggressive behavior (p=0.000). In conclusion, there is no relationship between online game addiction and adolescent self-identity; there is a significant relationship between online game addiction and social interaction, which causes aggressive behavior in adolescents. Keywords: Online Games, Self Identity, Social Interaction, Aggressive Behavior, Adolescents